1976
DOI: 10.1093/infdis/133.1.57
|View full text |Cite
|
Sign up to set email alerts
|

A Rhesus Monkey Model for the Study of Bolivian Hemorrhagic Fever

Abstract: Two groups of rhesus monkeys were inoculated with either 10(5) (group 1) or 10(3) (group 2) plaque-forming units of Machupo virus, the etiologic virus of Bolivian hemorrhagic fever. The monkeys were observed for clinical signs; body temperatures, viremias, hematologic changes, and virus-neutralizing antibody were measured. The onset of clinical signs for groups 1 and 2 occurred on days 4-6 and 7-10, respectively, with fever, anorexia, and depression. These and other signs became more severe, and all of the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…During the development of this system, we also generated a minigenome (MG) reporter system, which allowed us to study the cis-and trans-acting factors required for MACV replication and gene expression in a BSL-2 environment without select agent restrictions, therefore enhancing our capabilities for potential virus replication studies and drug screening. And finally, we have identified a novel murine model of MACV-induced LNS, similar to what is described in reports of infected humans and NHPs (34)(35)(36). This is the first reported model of LNS in a murine species infected with a New World arenavirus.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…During the development of this system, we also generated a minigenome (MG) reporter system, which allowed us to study the cis-and trans-acting factors required for MACV replication and gene expression in a BSL-2 environment without select agent restrictions, therefore enhancing our capabilities for potential virus replication studies and drug screening. And finally, we have identified a novel murine model of MACV-induced LNS, similar to what is described in reports of infected humans and NHPs (34)(35)(36). This is the first reported model of LNS in a murine species infected with a New World arenavirus.…”
supporting
confidence: 78%
“…challenge, but the disease development has not been well characterized (9,22). Studies utilizing "chaired" NHPs reported lethal disease development following intradermal, intramuscular, and intranasal challenge (34)(35)(36). Interestingly, African green monkeys, rhesus macaques, and cynomolgus monkeys developed a lethal late neurological syndrome (LNS), a disease also reported in guinea pig models infected with JUNV (37).…”
mentioning
confidence: 99%
“…In previous studies, a ''2-phase'' disease was observed in rhesus and cynomolgus macaques challenged subcutaneously with hamster-adapted Caravallo strain of Machupo virus. 9,25,30,40 These studies characterized MACV disease progression in macaques by an initial acute phase beginning at 7 to 10 days postexposure with death occurring generally by the end of week 3. Clinical improvement in survivors of the acute phase occurred around day 21 and progressed for a subsequent 7 to 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine 211 is present in cat TfR1, a very efficient receptor for all three New World hemorrhagic fever arenaviruses. TfR1 from the rhesus macaque, a non-human primate model for MACV and JUNV infections (46,47), also has a tyrosine at position 211. In contrast, position 211 is an aspartic acid in house mouse and rat TfR1 orthologs, preventing efficient arenavirus entry.…”
Section: Discussionmentioning
confidence: 99%